4.8.out
z = x -> (y -> z) ]]>
z = x => (y => z) ]]>
y = x => (x => y) ]]>
def)") ]]>
(x => y) = x -> y ]]>
x = 1 ]]>
(y => z) = y => (x => z) ]]>
y) ^ (x => z) = x => (y ^ z) ]]>
y)) v y = y ]]>
y) ^ y = y ]]>
(y => z) = y => (x -> z) ]]>
((y v x) -> z) = x -> z ]]>
c3 != c1 -> (c2 -> c3) ]]>
(x => (y => z)) = (x * y) -> z ]]>
(y => (x => z)) = y => (x -> z) ]]>
(x ^ y) = 1 ^ (x => y) ]]>
(y -> (x => z)) = y -> (x -> z) ]]>
((x v y) -> z) = x -> z ]]>
x) = y => x ]]>
(x ^ y) = x => y ]]>
((y => x) -> z) = x -> z ]]>
(x => (y -> z)) = y -> (x -> z) ]]>
(y -> z) = y -> (x -> z) ]]>
(y -> z) = y -> z ]]>
(x -> z) = x -> z ]]>
((x ^ y) -> z) = (x ^ y) -> z ]]>
((y * (y => x)) -> z) = (y * (y => x)) -> z ]]>
(y => (x => (y => z))) = (x * y) -> z ]]>
(x => (y -> z)) = (x * y) -> z ]]>
z = x -> (y -> z) ]]>
(y -> ((y => x) -> z)) = (y * (y => x)) -> z ]]>
(y -> ((x => y) -> z)) = (x * (x => y)) -> z ]]>
y)) -> z = x -> (y -> z) ]]>
((x => y) -> z) = x -> (y -> z) ]]>
((x => y) -> z) = x -> ((x ^ y) -> z) ]]>
((x ^ y) -> z) = x -> (y -> z) ]]>
z = x -> (y -> z) ]]>